2017
DOI: 10.2174/1573406413666170307163929
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico Studies of Mangiferin from Aphloia theiformis on Key Enzymes Linked to Diabetes Type 2 and Associated Complications

Abstract: This study provided an insight of the molecular interaction of mangiferin with the studied enzymes and can be considered as a valuable tool for designing new drugs for better management of these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The results showed that mangiferin bonds to both allosteric and orthosteric sites by p-p interactions. In addition, the difference in the fitness value found for the docking at the allosteric site (68.11) with that in the orthosteric site (59.11) is in agreement with a noncompetitive type of inhibition [92].…”
Section: Compsupporting
confidence: 57%
“…The results showed that mangiferin bonds to both allosteric and orthosteric sites by p-p interactions. In addition, the difference in the fitness value found for the docking at the allosteric site (68.11) with that in the orthosteric site (59.11) is in agreement with a noncompetitive type of inhibition [92].…”
Section: Compsupporting
confidence: 57%
“…The observed enzyme inhibitory activity of B. speciosa stem bark methanol extract might be related to more than one phytochemical that is present in the extracts. Interestingly, molecular docking studies have previously shown that mangiferin effectively binds to acetylcholinesterase and butyrylcholinesterase [45]. Ferulic acid was reported to hybridise with quinoline in a competitive manner.…”
Section: Resultsmentioning
confidence: 99%
“…Natural bioactive compounds from plants extracts, either as pure compounds or as standardized extracts, are of increasing interest for their versatile applications in pharmaceutical, nutraceutical and cosmetic industry. For this purpose, specific extraction techniques are essentially required to ensure isolation of specific bioactive constituents, to optimize the concentration of known constituents and also to maintain their biological activities …”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, specific extraction techniques are essentially required to ensure isolation of specific bioactive constituents, to optimize the concentration of known constituents and also to maintain their biological activities. [2][3][4] Extraction is one of the most important steps in the flowchart of phytochemical studies to obtain bioactive components. The choice of a suitable extraction method (with solvents and standardized process) are required for extraction of desirable constituents.…”
Section: Introductionmentioning
confidence: 99%